The Design of the Action Project in Work-Based Learning - Joseph A. Raelin (Human Resource Planning, 1999)
This paper attempts to remedy the inattention heretofore paid to the action project in the work-based learning literature. It begins with the assertion that there can be no substitute for real-time experience in human resource planning and development programs. Action projects afford real-time experience by involving participants in concrete actions typically in their own organization. The projects are designed to have strategic value, thus contributing to or even challenging the goals of their organizational sponsor. While working on their project, participants engage in both individual and collective learning, results deemed as important as the business outcomes of their project intervention. The article goes into considerable detail noting the benefits but also the pitfalls of action projects.
Keywords: I2; I21; M10; M12; M53; O15; 330; Action learning; Action project; Facilitation; Learning team; Reflection; Work-based learning